Induction of cyclic AMP phosphodiesterase in Blastocladiella emersonii and its relation to cyclic AMP metabolism. - Epstein, P M (1978)
Extracts of vegetative cells of Blastocladiella emersonii contain 5% or less of the cyclic AMP phosphodiesterase activity in zoospore extracts. This difference in activity could be accounted for entirely by an increase in the differential rate of phosphodiesterase synthesis during sporulation, beginning after a lag period of about 60 min and extending for at least an additional 90 min into the 4-h sporulation process. To examine the relation between enzyme synthesis and cyclic nucleotide metabolicm, we determined the substrate specificity of phosphodiesterase synthesized during sporulation and partially purified from zoospores. Zoospore extracts contain two components, separable by gel filtration chromatography, with cyclic AMP phosphodiesterase activity. The larger component accounts for 20% of the total activity and the smaller component for 80%. Both components show essentially an absolute substrate specificity for cyclic AMP among several cyclic purine and cyclic pyrimidine nucleotides tested. Nevertheless, we found no change in the total cyclic AMP content of sporulating cells before, during, or after enzyme activity increased. We speculate that some other component of cyclic AMP metabolism or function limits the rate of cyclic AMP hydrolysis in sporulating cells.